Implementasi Manajemen Pendidikan dalam Membentuk Karakter Religius Siswa di Raudathul Athfal Pesantren Ilmu Quran (PIQ) Sangatta Utara - Ari Rahayu; Ramdani Mubarok; Jumrianah Jumrianah (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
Education is a crucial process in shaping character and developing students' potential holistically, including the religious aspect, which is essential to instill from an early age. This study is motivated by the importance of educational management in systematically implementing religious character formation, particularly at Raudhatul Athfal Pesantren Ilmu Quran (PIQ) Sangatta Utara. The purpose of this research is to identify students' religious character, the implementation of educational management, and the challenges faced in forming religious character at RA PIQ. This study uses a descriptive qualitative approach with data collection techniques including observation, interviews, and documentation. The informants in this study were the principal and teachers at RA PIQ. The data analysis technique used is the Miles and Huberman model, which includes data reduction, data display, and verification. The findings indicate that religious character formation is carried out systematically through collaboration between the school and parents, using learning approaches, routine practices, and extracurricular programs. The implementation of management is based on the theories of Mazmanian and Sebastier as well as Nawawi's concept, integrated with the Merdeka Curriculum and the Pancasila Student Profile Strengthening Project (P5). Despite challenges, active parental involvement and teacher diversity serve as key supporting factors.